Penerapan E-LKPD Berbantuan Liveworksheet Pada Materi Daur Biogekimia Kelas Ⅹ SMA Negeri 01 Pekanbaru - Dira Yanti; Finanta Okmayura; Eliya Mei Sisri (Lembag, 2024)
One of the varied learning media tha can be applied is E-LKPD learning media. LKPD contains a task sheet, instructions, learning evaluations given to students that are formed in accordance with the competencies which is formed in accordance with the basic competencies basic competencies of the material contained in the LKPD. This study aims to determine the effect of using E-LKPD assisted by Liveworksheet on student learning outcomes in Biogeochemical Cycle material in class X SMA Negeri 01 Pekanbaru. This study used a quasi-experimental research design with Posttest Only Control Group Design. The population in this study were class X students even semester of the 2024 academic year consisting of class X-5 students as the control class and class X-1 as the experimental class. The results showed that there was a significant difference between the learning outcomes of experimental class students who used E-LKPD assisted by Liveworksheet and the control class that did not use E-LKPD. This is indicated by the average value of student learning outcomes of the experimental class (88.675) which is higher than the control class (72.476).